2019
DOI: 10.1111/cts.12643
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Association Analysis Reveals Variants Associated With Blood Pressure Response to Beta‐Blockers in European Americans

Abstract: European Americans (EA) have a better antihypertensive response to β‐blockers when compared with African Americans, albeit with some variability. We undertook a genomewide association study to elucidate the underlying genetic determinants in EA contributing to this variability in blood pressure (BP) response. A discovery genomewide association study of change in BP post–metoprolol treatment was performed in EA participants (n = 201) from the Pharmacogenomic Evaluation of Antihypertensive Responses‐2 (PEAR‐2) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Given that black subjects have different antihypertensive responses to β-blockers compared to Caucasians, recent GWAS have focused on this last population 41,64,65. Hiltunen et al identified the SNPs rs2514036, rs948445, and rs2514037 in the ACY3 gene (coding for aminoacylase III) associated with blood pressure responses to the β‑blocker bisoprolol in Caucasians 41.…”
Section: β-Blockersmentioning
confidence: 99%
“…Given that black subjects have different antihypertensive responses to β-blockers compared to Caucasians, recent GWAS have focused on this last population 41,64,65. Hiltunen et al identified the SNPs rs2514036, rs948445, and rs2514037 in the ACY3 gene (coding for aminoacylase III) associated with blood pressure responses to the β‑blocker bisoprolol in Caucasians 41.…”
Section: β-Blockersmentioning
confidence: 99%
“…Although blood pressure has a high degree of heritability, genetic variants identified to date explain only a small percentage (~<3%) of the interindividual variation in blood pressure . Candidate gene and genome‐wide studies have identified pharmacogenetic variants associated with the BP‐lowering response to antihypertensive medications (particularly thiazide diuretics [ NEDD4L] and beta blockers [ ADRB1] ) although the effect sizes of individual variants are quite small . However, the effectiveness of antihypertensive medication does vary by ancestral group (eg, African, Asian, and European ancestry), which may be related, in part, to genetic factors that vary in frequency according to historical geographic separations (ie, Europeans, Asians, and Africans living partially isolated in unique environments for tens of thousands of years) .…”
Section: Discussionmentioning
confidence: 99%
“…GRK4 65L and 142V are associated with reduced BP responses to atenolol in both Caucasians and African Americans [ 66 ]. In a genome-wide association study of metoprolol treated individuals from the Pharmacogenomic Evaluation of Antihypertensive Responses-2 (PEAR-2) study and atenolol treated subjects from the PEAR study, rs294610 (an intronic SNP resulting in C/A transversion) in the FGD5 gene (encoding FYVE, RhoGEF, and the PH domain containing protein 5) was found to significantly improve BP response following metoprolol and atenolol treatment (the latter analysis was carried out in an independent cohort of European Americans) [ 68 ]. Carriers of the A allele had considerably better BP responses than non-carriers.…”
Section: β-Adrenergic Antagonists (β-Blockers)mentioning
confidence: 99%
“…However, further studies are necessary to understand the functional role of SNPs within the FGD5 gene in improved BP responses to β-blockers. In turn, in an analysis of the results obtained from two studies (PEAR-2 and PEAR) with an independent atenolol add-on therapy, Singh et al [ 68 ] identified rs45545233 polymorphism in the SLC4A1 gene, which was significantly associated with a reduced BP response to β-blockers. The PEAR-2 metoprolol-treated cohort analysis also found the SLC4A1 gene encoding for glycoprotein in the plasma membrane (the band 3 anion transporter belonging to the anion exchanger family) to be related to drug response.…”
Section: β-Adrenergic Antagonists (β-Blockers)mentioning
confidence: 99%
See 1 more Smart Citation